2010
DOI: 10.1186/1742-4690-7-85
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-associated differences in HIV-1 reverse transcription affect the viral replication

Abstract: BackgroundThe impact of the products of the pol gene, specifically, reverse transcriptase (RT) on HIV-1 replication, evolution, and acquisition of drug resistance has been thoroughly characterized for subtype B. For subtype C, which accounts of almost 60% of HIV cases worldwide, much less is known. It has been reported that subtype C HIV-1 isolates have a lower replication capacity than B; however, the basis of these differences remains unclear.ResultsWe analyzed the impact of the pol gene products from HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 73 publications
(94 reference statements)
2
27
0
Order By: Relevance
“…We observed a strong inhibitory effect of PPYaT on cultured T cells infected with HIV-1 subtype B, but less so with HIV subtype C. Previously, subtype C was shown to exhibit slower replication due to a different enzymatic activity of its reverse transcriptase (45). Thus, iron chelators may not be efficient against all HIV subtypes, and whether they have an effect on other HIV subtypes remains to be determined.…”
Section: Discussionmentioning
confidence: 66%
“…We observed a strong inhibitory effect of PPYaT on cultured T cells infected with HIV-1 subtype B, but less so with HIV subtype C. Previously, subtype C was shown to exhibit slower replication due to a different enzymatic activity of its reverse transcriptase (45). Thus, iron chelators may not be efficient against all HIV subtypes, and whether they have an effect on other HIV subtypes remains to be determined.…”
Section: Discussionmentioning
confidence: 66%
“…A recent study by Iordanskiy et al (18) found that differences in the replicative fitness of subtype B and C RTs is linked to the polymerase and the RNase H domain of RT. These findings cannot explain why some NNRTI resistance mutations are nonfunctional in the MJ4 background RT, since the RNase H and connective domains remained constant in all clones tested regardless of RT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Over half of the global HIV population is infected with subtype C, 4,29,30 which is dangerously uncontrolled in Africa and India. Subtypes A and B follow, then CRF_AG and CRF_AE, the latter predominantly found in Asia.…”
Section: Hawke Et Almentioning
confidence: 99%